The History of human rights: from ancient times to the globalization era - Ishay, Micheline R. (Micheline Rose) (University of California Press, 2004)
"Micheline Ishay recounts the dramatic struggle for human rights across the ages in a book that brilliantly synthesizes historical and intellectual developments from the Mesopotamian code of Hammurabi to today's era of globalization. As she chronicles the clash of ideas, social movements, and armed conflicts that have played a part in this struggle, Ishay ilustrates how the concept of human rights has evolved from one era to another through texts, cultural traditions, and creative expression. Writing with verve and extraordinary range in the only comprehensive history of human rights available, she develops a framework for undestading contemporary issues from the debate over globalization to the intervention in Kosovo to the post-September 11 climate for human rights.."